Nursing students' evaluation of clinical learning environment and supervision in a Norwegian hospital placement – A questionnaire survey using CLES+T scale. (July 2021) - Johannessen, Anne-Kari; Barra, Mathias; Vullum, Sylvi; Werner, Anne
Abstract: Aim: The clinical learning environment and supervisor-student relationship play vital roles in the learning outcomes of nursing students. The aim of this study is to evaluate nursing students' experiences with the clinical learning environment and supervision in a hospital placement organised with a dual preceptor team – preceptors holding dual positions both in the clinic and the nursing faculty in addition to the standard one-to-one supervision by a clinical preceptor. Design: The study is a paper-based survey based on a validated questionnaire developed and tested in hospital settings in various European countries, including Norway. Method: The Norwegian version of the CLES+T Evaluation Scale, was distributed to all second-year students in three different years (2015–2017) at a nursing faculty. Results: A total of 61% students ( n = 261 ) returned the questionnaire. Overall, the students considered that their hospital placement provided a good clinical learning environment. The results suggest that the dual preceptor team on top of one-to-one supervision did not interfere negatively with the clinical learning environment Nevertheless, the dual preceptor model did not compensate for a poor relationship with the clinical preceptor. Thus, the association between a reported 'strained relationship' with the clinical preceptor and low scores on the CLES+T, reported on by other studies, remained in our data. Conclusions: To better grasp the complexity in this area, various methods are needed, such as in-depth interviews with students, nurse teachers and clinical preceptors. Further studies need to elaborate on students' experiences of clinical learning environment according to how supervision is organised. Highlights: Nurse students evaluated the clinical learning environment with dual preceptor team as positively. Stable one-to-one supervisory relationships were highly valued. Future studies about organising of supervision and clinical learning environment is recommended.